Clinico-epidemiological profile of congenital heart disease in a tertiary care center – a retrospective descriptive study - Dr. Pramila Ramawat; Dr. Nilesh Jain (Pediatric Review: International Journal of Pediatric Research, 2020)
Aims and objective: To study the clinical-epidemiological profile of congenital heart disease in hospitalized children.Material and methods: A retrospective study was planned in a tertiary care center in Central India. Children between ages 1 month to 14 years with CHD were included in this study. Type of CHD, clinical presentation, anthropometry, demographic profile, and the outcome was recorded.Result: A total of 65 patients were included in the study. 43 patients were suffering from acyanotic CHD and 22 were having cyanotic CHD. Most of the children admitted were below 1 year of age (n-67%). Males (42) were more reported in the present study than females (23).Conclusion: CHDs are one of the commonest birth defects, timely diagnosis and intervention are very important to decrease mortality and morbidity in pediatric patients.